AMGra: uma abordagem para migração gradativa de aplicações legadas - Fontanette, Valdirene (Universidade Federal de São Carlos, 2005)
Along the time the applications usually need to evolve to catch up with and to assist to the new technologies that appear or get mature in the different computing areas, as it happens, for instance, with the programming languages. Starting from that demand, new researches are being accomplished to offer support to this development. This situation was improved with the ripening of Web technologies, once the need of the company nowadays is not always to convert an application totally, but to adapt these applications to accommodate these new technologies. The modernization of old applications, denominated legacy applications, is an arduous and a high cost task for the companies. Although there are several approaches that support this process in the literature, there is still a lack of resources that offer flexibility, take advantage of previous investments of the companies and get practical results. This way, the modernization process in the companies is almost always accomplished in a manual and "ad-hoc" form. Based on these ideas, this work presents AMGraA, an approach for gradual modernization of legacy applications, reconstructing them to attend to new technologies that came out along the time. This research project resulted of a partnership among GOES (Group of Software Engineering), a software development company, and FAPESP in support to the research and the development in the small companies.
Keywords: Engenharia de software; Reengenharia orientada a objetos; Sistemas de transformação de software; Integração de sistemas; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO